Ранняя диагностика и профилактика болезней кровообращения в условиях экологического неблагополучия - Кирсанова, Е. В.; Кондратенко, А. А.; Кірсанова, Олена Валентинівна; Kirsanova, E. V.; Kondratenko, A. A. (My University, 2016)
Проанализировав функциональное состояние организма, используя метод анализа вариабельности сердечного ритма, мы можем обосновать необходимость использования в профилактических медицинских осмотрах методов, которые направлены на повышение защитных свойств и устойчивости организма человека к вредному воздействию факторов окружающей среды. This article is devoted to the study of the effectiveness of early diagnosis and prevention, which will help prevent circulatory system disease in disadvantaged ecological regions. After analyzing the functional state of the body, using the method of analysis of heart rate variability, we can identify and justify the need for preventive medical examination methods, which aim to increase the protective properties of the human body and resistance to harmful environmental factors.
Early diagnosis and prevention of cardiovascular diseases on the ecological adversity territory
Keywords: тезы